ANALISIS DISPARITAS PEMBANGUNAN EKONOMI DAN HUBUNGANNYA DENGAN INVESTASI DI PROVINSI SUMATERA BARAT TAHUN 2017-2021 - Bashrihan Bashrihan; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
Inequality between regions is closely related to economic development problems. Where differences in economic capacity between regions and uneven investment realization are the drivers of inequality between regions. This study aims to analyze disparities in economic development and their relationship with investment in West Sumatra Province in 2017-2021. The method used in this study is descriptive quantitative with data collection techniques carried out by means of documentation and the data used is secondary data originating from the BPS of West Sumatra Province and the National Single Window for Investment (NSWI). The results of the Williamson Index show that development inequality in West Sumatra Province in 2017-2021 with an average of 0.280 is classified as low inequality but during this period has increased regularly and consistently. Based on the results of the Pearson correlation test, the relationship between disparity and investment, which is divided into Domestic investment and Foreign Investment, has a very strong relationship with a correlation coefficient of 0.817 with Domestic investment and -0.915 with Foreign Investment